THE ECOLOGICAL POLICY AS AN INSTRUMENT OF AIR TRANSPORTATION ENVIRONMENTAL IMPACTS MINIMIZATION - Radomska, Margaryta; Sahaydak, Margarita (Proceedings of National Aviation University (archive), 2018)
Purpose. The paper presents the analysis of the aviation impacts on the environment and the recommendations on development of environmental policy for airlines aimed at environmental performance improvement. The analysis of the latest research and publications. The problems of aviation interaction with environment are provided with targeted research efforts by all major regulators of the industry, but it is also important to analyze the current environmental policies of airlines to get insights of how airlines understand the environmental problems of their industry and evaluate their willingness to solve them.. The modern trends in aviation development. The world passenger air transportations are expected to grow up to 2030s. Statistical data on activity of the biggest national airports in Ukraine also shows the positive tendency in number of flights during the last three years. The analysis of environmental impacts of aviation. The growth of aviation raises the problem of environmental impacts, including contribution to climate changes; pollution of the ground atmosphere, soils and surface waters; noise pollution; wastes accumulation; threats to the habitats and diversity; reduction of arable lands; consumption of water and energy; electro-magnetic pollution; health effects, etc. The purpose and essence of environmental policy for airlines. An environmental policy is a presentation of airlines aims and principles in managing the environmental effects. It helps to develop the positive external image of the company. The analysis of the airlines environmental policies in action. The analysis of environmental policies of over 40 air companies from various parts of the world found that the content of all policies is almost the same with differences related to priorities setting and and site specific environmental concerns. Discussions. There are some serious drawbacks in the environmental policies considered: declarative character of the policies’ provision, absence of planned procedures for progress evaluation and redistribution of responsibilities to passengers. Conclusions. To combat the negative environmental issues of airlines activity the system of environmental management must be implemented based on the efficient environmental policy, which includes clear realistic targets with numerical presentation of potential progress.